Electrical compensation for shape distortion of large phased array under combined loads - Shunxi Lou; Wei Wang; Naigang Hu; Hong Bao; Xiangtao Hu; Zhihai Wang (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2017)
Mechanical error of the phased array antenna in practice will affect its radiation performance. In this paper, a least square error method (LSE) was proposed to compensate the radiation performance of the distorted phased array antenna. To demonstrate and validate our method, pattern compensation in a large planar phased array antenna is carried out.